CSR and firm profitability: Evidence from a meta-regression analysis - Stefan Hirsch; Thies Petersen; Maximilian Koppenberg; Monika Hartmann (Journal of Economic Surveys, 2022)
We analyze the literature on the relationship between corporate social performance (CSP) and corporate financial performance (CFP) by applying meta-regression analysis (MRA) to 7800 results of 512 empirical studies. Our findings reveal a small positive link between CSP and CFP as well as the presence of publication bias that favors statistically significant CSP–CFP regression coefficients. We also evaluate the impact of the underlying research design on the heterogeneity in published effects using Bayesian and frequentist model-averaging (FMA). We consider 42 contextual characteristics and our results show that reported CSP–CFP effects are smaller in cases where a binary index is used to measure CSP or when CSP is used as the dependent variable. In contrast, firms in industrial sectors or operating in China rather than the United States exhibit stronger effects. Finally, the CSP–CFP effect is driven by the choice of the econometric estimator and the inclusion of firm size as control variable.
Keywords: 330; corporate social responsibility; firm profit; meta-regression; publication bias